Measuring and analyzing the impact of public spending and some macroeconomic variables on poverty rates for the period 1990-2020 using the Autoregressive Distributed Lag model (ARDL) (Iraq case study) - Saeed, Dindar Issa; Daher, Abdulhamid (Humanities Journal of University of Zakho, 2023)
The study aims to measure and analyze the impact of public spending and some macroeconomic variables on the poverty rate in Iraq during the period of 1990 to 2020. Annual data has been obtained from the official sources. The study included a number of macroeconomic variables which are; Real GDP, unemployment, inflation, population growth rate, and income inequality as well as public spending.The study hypothesized that there is a statisticaly inverse relationship between the poverty rate and the variables (public spending and real GDP growth rate), and a positive relationship between the poverty rate and the variables (inflation, unemployment, population growth rate, and and income inequality). The study used the descriptive analytical approach in the theoretical aspect as well as the quantitative approach in the applied aspect by using the Autoregressive Distributed lag (ARDL). The study concluded that there is an insignificant positive relationship between public spending and the poverty rate. The study also revealed that there is a significant inverse relationship between the poverty rate and the rate of GDP growth, and a positive and significant relationship between the poverty rate, inflation rate, population growth rate and the income inequality. In addition there is an insignificant inverse relationship between the poverty rate and the unemployment rate. Finally, the study concluded with a set of recommendations, the most important of which is the restructuring of public spending to support the poor by providing social services such as education, health and safe drinking water, and the need for the state to implement economic development projects and raise economic growth rates in order to increase national income on the one hand and increase the income of the poor on the other hand, Focusing on reducing inequality in income distribution.